Normative data of Visual Evoked Potential in children and correlation with age - Yadav, Renu; Poudel, Bishnu Hari; Limbu, Nirmala; Thakur, Dilip; Yadav, Subodh Kumar (Asian Journal of Medical Sciences, 2015)
Background: Visual Evoked Potential is the assessment of the visual pathway and the visual cortex. The present study was descriptive analysis of normal VEP between the age of 6 months to 4 years of age and the determination of the neuronal development among healthy children of above age group. Materials and Methods: The study was conducted in neurological lab of BPKIHS on healthy children (n=36) of well-baby clinic between the age of 0.5 to ≤4 years (yr). Subjects were divided into subgroup 1(0.5 to ≤2 yr), subgroup 2(2 to ≤3 yr) and subgroup 3(3 to ≤4 yr). Visual stimulator provided with flash light emitting diode (LED) goggle was used to stimulate the retina and VEP recording was done. Flash VEP parameters: latencies (N90, P120) and amplitude (N90-P120) were recorded. Post hoc (Bonferroni) analysis was done for comparing VEP variables. Pearson correlation and scatter plot with trend line analysis were done for VEP with respect to age Results: VEP latencies of children, age-group 3 to Μ4 yr showed significantly less N90 latency on right eye stimulation comparing age-group 0.5 to Μ2 yr (103.75±22.54 vs. 79.09±17.77ms, p=0.012). P120 latency was significantly less on right eye stimulation (148.5±15.38 vs. 116.67±13.65ms p=0.001) and on left eye stimulation (145.91±18.11 vs. 116.67±13.65 ms, p=0.001) in age-group 3 to Μ4 yr children as compared to age-group 0.5 to Μ2 yr. Conclusion: Significant decrement of VEP latencies as age advances which explains the maturation of central nervous system and functionally approaching to adult value at around 3 to 4 yr. Asian Journal of Medical Sciences Vol.7(2) 2015 39-43